The impact of multimorbidity on severe COVID-19 outcomes in community and congregate settings - Anna Pefoyo Kone; Lynn Martin; Deborah Scharf; Helen Gabriel; Tamara Dean; Idevania Costa; Refik Saskin; Luis Palma; Walter P. Wodchis (Elsevier, 2023)
Purpose: This study examined the impact of multimorbidity on severe COVID-19 outcomes in community and long-term care (LTC) settings, alone and in interaction with age and sex. Methods: We conducted a retrospective cohort study of all Ontarians who tested positive for COVID-19 between January-2020 and May-2021 with follow-up until June 2021. We used cox regression to evaluate the adjusted impact of multimorbidity, individual characteristics, and interactions on time to hospitalization and death (any cause). Results: 24.5% of the cohort had 2 or more pre-existing conditions. Multimorbidity was associated with 28% to 170% shorter time to hospitalization and death, respectively. However, predictors of hospitalization and death differed for people living in community and LTC. In community, increasing multimorbidity and age predicted shortened time to hospitalization and death. In LTC, we found none of the predictors examined were associated with time to hospitalization, except for increasing age that predicted reduced time to death up to 40.6 times. Sex was a predictor across all settings and outcomes: among male the risk of hospitalization or death was higher shortly after infection (e.g. HR for males at 14 days = 30.3) while among female risk was higher for both outcome in the longer term (e.g. HR for males at 150 days = 0.16). Age and sex modified the impact of multimorbidity in the community. Conclusion: Community-focused public health measures should be targeted and consider sociodemographic and clinical characteristics such as multimorbidity. In LTC settings, further research is needed to identify factors that may contribute to improved outcomes.